The Influence of the Quality of Passport Production Services on Community Satisfaction at Class II Imgration offices Atambua Immigration Check Places - FATIN, Donatus Gin; LILIWERI, Aloysius; NEOLAKA, Melkisedek N.B.C. (PT Keberlanjutan Strategis Indonesia, 2024)
This research describes the quality of passport-making services at the TPI Atambua Class II Immigration Office. This research focuses on passport-making services because they have the most applicants. This problem occurs because passport completion exceeds standards and employee information is unclear. This research was a quantitative descriptive study with 96 respondents, using purposive and incidental nonprobability sampling models. The research results show that the quality of service on community satisfaction at the TPI Atambua Class II Immigration Office has a value of 0.463, which means (46.30%). Obtained from five dimensions of service quality, such as physical evidence of (0.139), reliability dimension (0.126), responsiveness dimension (0.007), assurance dimension (0.096), and empathy dimension of (0.120). The simultaneous test shows an F-count of 11.255, confirming the significant relationship between the five dimensions of service quality and community satisfaction. This research suggests that the five dimensions of service quality simultaneously have a significant effect on community satisfaction at the TPI Atambua Class II Immigration Office